Hubungan Gaya Komunikasi Manajemen Kepada Bawahan dengan Kepuasan Kerja Pegawai PT. Casurindo Siperkasa Kota Medan - Dermawan, Tengku Ferry; Syafrizaldi, Syafrizaldi (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
This study aims to determine the relationship between the management communication style of PT. Carsurindo Siperkasa and employee job satisfaction. This type of research is quantitative research with a correlational approach. The population in this study were employees at PT. Casurindo Siperkasa and the Management of PT. Casurindo Siperkasa totaling 35 people. The sampling technique used total sampling (saturated sampling), which is a sampling technique where all members of the population are used as samples. The sample used was the entire population of 35 people. Data collection techniques used questionnaires and field observations. Data analysis techniques were instrument trials, descriptive data analysis, coefficient of determination and hypothesis testing using the Spearman Rank correlation method. The results of the study obtained a Spearman rank correlation value of 0.885. Spearman rank correlation score shows that there is a strong relationship between Superior to Subordinate Communication Style and Employee Job Satisfaction at PT. Casurindo Siperkasa. The results of the hypothesis test obtained a Significance value (Sig) of the communication style variable (X) of 0.000. Because the Sig. value is 0.000 0.05, it can be concluded that Ha is accepted and Ho is rejected. This means that there is a positive relationship between communication style (X) and Employee Job Satisfaction (Y). The relationship between Superior to Subordinate Communication Style and Employee Job Satisfaction is 79.5%.